Analisis Efektivitas Metode Responsible, Accountable, Consulted, Informed (RACI) dalam Sistem Manajemen Process Approval - Dianni Yusuf; subono subono (Prodi Teknik Elektro Universitas PGRI Banyuwangi, 2025)
The approval management process plays an essential role in improving efficiency and accountability in organizational decision-making. PT Asta Berkah Autonomous, a company specializing in automation system development, faces challenges in transparency and efficiency due to manual approval procedures conducted through Google Forms and email. This study aims to design and implement a web-based approval management system integrated into the Asta Project application using the Responsible, Accountable, Consulted, Informed (RACI) method. The RACI method is applied to clearly define the roles and responsibilities of each stakeholder, ensuring a structured and transparent approval workflow. The system development process adopts the Rapid Application Development (RAD) approach, emphasizing iterative design and user involvement. System testing was conducted using Blackbox Testing and User Acceptance Testing (UAT) based on ISO 9126 quality standards. The results demonstrate that the implementation of the RACI method enhances role clarity, process efficiency, and transparency among participants. The developed system successfully reduces submission time, simplifies approval tracking, and supports faster and more accurate decision-making. This implementation significantly contributes to improving productivity and governance of the approval process within PT Asta Berkah Autonomous. System testing using Blackbox Testing and User Acceptance Testing (UAT) based on ISO 9126 quality standards. The results show that all system functions operated successfully (100% valid), with an average user satisfaction score of 84.44%, categorized as excellent. The application of the RACI method significantly improved efficiency, transparency, and accountability in the company’s approval process. Overall, the developed system contributes to digital transformation efforts and enhances corporate governance effectiveness.